Translanguaging as Resilience: Trauma-Informed and Culturally Sustaining Education for Venezuelan Indigenous Refugee Students in Brazil’s Public Schools - Oliveira de Paula, Karina; Angelo-Rocha, Michelle; Janerrandra, Maria; de Oliveira, Cátia Regina Guidio Alves (International Electronic Journal of Elementary Education, 2026)
This qualitative case study examines how Café Sem Troco, a rural public school near Brasília in Brazil’s Central West region, supported Warao Indigenous refugee students from Venezuela through translanguaging and trauma-informed, culturally sustaining pedagogy. Data were collected in 2024 and 2025 through five in-depth interviews with teachers, the school leader, and a Warao community leader; analysis of participant-generated photographs and short videos; and extensive participant follow-up. Guided by a critical, qualitative, and community-based research approach, we used thematic analysis to interpret interviews and visual artifacts. Findings identify three areas: educator responses to forced displacement; the schooling effects of poverty, food insecurity, and nutritional trauma; and acculturation pressures shaping students’ self-esteem. Educators built a multilingual, relational classroom where Warao, Spanish, Portuguese, and Brazilian Sign Language (Libras) coexisted. Translanguaging functioned as an emotional, cultural, and instructional foundation, as well as a social justice-based practice that affirmed students’ and families’ identities, reduced anxiety, and strengthened belonging. Daily practices such as community food gathering, oral storytelling, and collective care resisted assimilation and honored Warao epistemologies and funds of knowledge. This study advances scholarship on Indigenous education and educational responses to forced migration, trauma, and hunger. It provides recommendations for policies, practices, and processes in public education, and outlines directions for future research.